HUBUNGAN ANTARA POLA ASUH OTORITER DENGAN KEMANDIRIAN REMAJA DI SMA NEGERI 1 SINGKOHOR KABUPATEN ACEH SINGKIL - Sinarsi Meliala; Siska Dwi Ningsih; Indomora Siregar (JURNAL PSYCHOMUTIARA, 2022)
Adolescent independence is an effort to be able to do something according to his own wishes. One of the factors that influence independence is parenting, especially otoriter parenting, otoriter parenting is a form of parenting with otoriter style emphasizing the obedience of a child to the rules they make, otoriter parenting with the characteristics of an otoriter person. parents have dominant power, parents will punish children who do not obey them, parents tend not to listen to the opinions of children so that children do not have a role at home, parents have very tight control over children's behavior. This study is a correlation study to determine the relationship between otoriter parenting and adolescent independence at SMA Negeri 1 Singkohor. The subjects in the study were 75 students from SMA Negeri 1 Singkohor. This research uses random sampling technique. The measuring instrument used in this study used a scale of otoriter parenting and a scale of independence. Analysis of the data used in this study using a computer statistical program with Spearman Rank correlation analysis to measure the relationship between otoriter parenting and independence. From the calculation results show a significance value of p-velue = 0.963 > (0.05) it can be concluded that there is no relationship between otoriter parenting and adolescent independence.